Soil Suitability Index for Sal (Shorea Robusta) Natural Regeneration - Seth, S. K.; Bhatnagar, H. P. (Indian Forester, 1959)
Soil culture experiments were conducted to determine desirable soil properties for securing good sal regeneration and the relation of comparative growth data to the status, good or deficient, of sal regeneration in the localities from which the samples are derived. The study revealed that the North Kheri good regeneration area soil is significantly superior to all the others in all characters except leaf area increment and even in this regard it shows the maximum development. Within the range of this study then, this soil may be taken as the ideal from the point of view of sal, and other soils may be rated accordingly as they approximate to or depart from this soil in various properties. All the soils originating from deficient regeneration areas are inferior to those originating from good regeneration areas, except for Bahraich soil from good regeneration area. A critical examination of all the soil determinations, i.e., mechanical, physical and physico-chemical, reveals that of the 14 characters, only soil pH, soil moisture in situ, water holding capacity, moisture equivalent and organic matter show indications of a definite relation to height increment, which has been selected as the index of suitability for natural regeneration. The range of dispersion of pH values is small and much reliance cannot be placed on moisture in situ which is largely dependent upon climatic conditions and therefore these two factors cannot be used as a basis for classifying soils with reference to development of sal seedlings. A statistical analysis was therefore carried out to test the multiple correlation between the remaining three factors (also including squared terms to provide for nonlinear effects, if any) and it was found that height increment could be expressed as a function of X, X2, y, y2 (where X is organic matter % and y is moisture equivalent %) each of which contributed significantly. Lower levels of organic matter and higher values of moisture equivalent indicate superior conditions for sal growth. Since organic matter too varies within comparatively low limits it was also investigated whether an equation using water holding capacity and moisture equivalent could be used. It was found that a linear relationship with moisture equivalent could be established. These relations emphasize the fundamental and domineering role played by water and the moisture retaining and releasing properties of the soils vis a vis sal natural regeneration.